Safeguarding Cultural Heritage and Promoting Economic-Cultural Growth in the Digital Era - Huang, Yonglin. author. aut Link
XXXIV, 316 p. 14 illus., 2 illus. in color.
Keywords: This book explores the impact of digital technology on the preservation and transmission of intangible cultural heritage and the evolution of cultural industries. The first section highlights the crucial role of digital technology in the protection and dissemination of intangible heritage. The second section theoretically analyzes the multifaceted relationships in the development of digital and cultural industry and examines the characteristics of cultural consumption in the digital economy era and its guidance, the role of 5G technology on driving innovation and advancing development in the cultural industry, and issues related to artificial intelligence and the digital cultural industry. The third section primarily discusses issues including the media revolution triggered by the development of new technologies, online communication and public opinion guidance, cyber-communities and social networking, as well as the construction of violence evaluation indices in video gaming. This book represents considerable theoretical and practical significance for advancing the digital protection and dissemination of intangible cultural heritage and enhancing the competitiveness of cultural industries through the application of digital technologies.